2018
DOI: 10.4314/ovj.v8i4.8
|View full text |Cite
|
Sign up to set email alerts
|

Molecular detection and characterisation of avian paramyxovirus type 1 in backyard chickens and pigeons in Alzintan city of Libya

Abstract: Avian paramyxovirus-1 (APMV-1) is the causative agent of Newcastle Disease which affects many species of birds leading to high mortality and heavy economic losses among poultry industry worldwide. Newcastle disease is endemic in Libya with frequent outbreaks occurring in commercial and backyard poultry. APMV-1 was isolated and characterised during the outbreak in 2013. In current study, we report another Newcastle disease outbreak that emerged in backyard chickens and pigeons in Alzintan city on March 2015. Tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…An exception is former sub-genotype VIIf that was classified as a separate sub-genotype, namely VII.1.2. The groups of viruses involved in the fifth NDV panzootic (VIIh and VIIi), that affected Indonesia, Asia, the Middle East, Europe, and Africa (Abolnik et al, 2018; Fuller et al, 2017; Kammon et al, 2018; Mapaco et al, 2016; Miller et al, 2015), lacked branch support, and were merged into a single sub-genotype VII.2. A group of five other sequences from viruses isolated in Namibia in 2016, previously identified as sub-genotype VIIk (Molini et al, 2017), were also assigned to VII.2 due to lack of branch support and insufficient number of independent isolates (Supplemental Fig.…”
Section: Resultsmentioning
confidence: 99%
“…An exception is former sub-genotype VIIf that was classified as a separate sub-genotype, namely VII.1.2. The groups of viruses involved in the fifth NDV panzootic (VIIh and VIIi), that affected Indonesia, Asia, the Middle East, Europe, and Africa (Abolnik et al, 2018; Fuller et al, 2017; Kammon et al, 2018; Mapaco et al, 2016; Miller et al, 2015), lacked branch support, and were merged into a single sub-genotype VII.2. A group of five other sequences from viruses isolated in Namibia in 2016, previously identified as sub-genotype VIIk (Molini et al, 2017), were also assigned to VII.2 due to lack of branch support and insufficient number of independent isolates (Supplemental Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The fourth NDV panzootic was caused by viruses of a single genotype (VII.1.1) that includes former sub-genotypes VIIb, VIId, VIIe, VIIj, and VIIl; sub-genotype VIIf is considered to be a separate sub-genotype, VII.1.2 [ 11 ]. The groups of viruses involved in the fifth NDV panzootic that affected Africa, Asia, the Middle East, and Europe [ 16 , 17 , 18 , 19 , 20 , 21 ], were merged into a single sub-genotype, VII.2, together with five other sequences identified as sub-genotype VIIk and then also assigned to VII.2 [ 22 ]. The predominant NDV sub-genotype in Egypt is VIId (VII.1.1), which has led to several outbreaks in poultry [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…This strategy has successfully reduced the threat of ND in commercial poultry but more outbreaks emerged in unvaccinated backyard birds. In March 2015, Kammon et al (2018) reported another ND outbreak in Alzintan city that emerged in backyard chickens and pigeons. The results of Kammon et al (2018) showed two viruses are genetically similar to those were isolated from cloacal swabs of backyard chickens in 2013, with a velogenic type of APMV-1 belongs to genotype VIb in a pigeon.…”
Section: Introductionmentioning
confidence: 99%
“…In March 2015, Kammon et al (2018) reported another ND outbreak in Alzintan city that emerged in backyard chickens and pigeons. The results of Kammon et al (2018) showed two viruses are genetically similar to those were isolated from cloacal swabs of backyard chickens in 2013, with a velogenic type of APMV-1 belongs to genotype VIb in a pigeon. Based on these results, it may indicate that NDV is still circulating in backyard birds which usually not vaccinated.…”
Section: Introductionmentioning
confidence: 99%